2017
DOI: 10.9788/tp2017.3-03en
|View full text |Cite
|
Sign up to set email alerts
|

Father Involvement: Construction of a Theoretical Model Based on a Literature Review

Abstract: An ample body of scientifi c evidence exists, documenting the importance of the father-child relationship. The objective of this study was to develop a theoretical model of father involvement, organized according to the principles of Structural Equation Modeling, which require specifi cation of the variables associated with the central construct, based on empirical data. In 2015, a systematic search was conducted in the databases APA PsycNET, Bireme, PEPSIC, Web of Science and IndexPsi Periódicos, using the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…In addition, when both parents engage in parenting programs, the outcomes for children are more positive [31]. A meta-analysis found that, compared to mothers, fathers have a greater ability to influence a child’s misbehaviors [32], and promotion of effective co-parenting enhances family functioning and child outcomes [33], but evidence on these father-related outcomes for children with disabilities is lacking [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, when both parents engage in parenting programs, the outcomes for children are more positive [31]. A meta-analysis found that, compared to mothers, fathers have a greater ability to influence a child’s misbehaviors [32], and promotion of effective co-parenting enhances family functioning and child outcomes [33], but evidence on these father-related outcomes for children with disabilities is lacking [34,35].…”
Section: Discussionmentioning
confidence: 99%